A temperature‐dependent hydrating structure around SO42− investigated from Raman spectroscopy. (5th April 2022) - Hu, Qingcheng; Zhao, Haiwen; Wu, Xiang'en; Liang, Yuying
Abstract: The Raman spectra of H2 O/D2 O−Na2 SO4 solutions are measured at temperatures ( T ) up to 573 K. The hydrating structure of SO4 2− is investigated based on the solute‐correlated (SC) OD/OH stretch bands obtained by the multivariate curve resolution method. Remaining a nearly constant wavenumber of the main peak with increasing temperature, the SC OD/OH bands are narrowed first due to the reduced relative intensity of the shoulder at 2395/~3245 cm −1 when T  < ~473 K/~513 K but then because the OD/OH bands get sunken around 2610/3580 cm −1 above ~473/~513 K (letting the ~2660/~3635 cm −1 mode be more prominent and even a separate peak). These spectral features incline to support a temperature‐dependent water structure in the SO4 2− hydration shell balanced by the SO4 2− ···H2 O(D2 O) and O–H(D)···O hydrogen bonds (those with D are stronger) as well as the electrostatics. Most hydrating water molecules are engaged in hydrogen bonding configurations of single donor (SD) and single hydrogen‐bond water (SHW). As temperature rises, the average number of hydrogen bonds per hydrating water molecule decreases below ~373 K because of the SD → SHW transition and increases afterward owning to the rapid increase of the ion pairs, and SO4 2− changes its role from structure breaker to structure maker above ~453 K. The temperature‐dependent solubility behavior of Na2 SO4 in H2 O can be rationalized by the ion pairing effect and temperature‐dependent structure details in SO4 2− hydration shell. Abstract : The Na2 SO4 ‐correlated Raman OD/OH stretch bands from 293 to 573 K suggest a temperature‐dependent water structure in SO4 2− hydration shell balanced by SO4 2− ···H2 O(D2 O) and O–H(D)···O hydrogen bonds and electrostatics. Most hydrating water molecules are engaged in hydrogen bonding configurations of single donor (SD) and single hydrogen‐bond water (SHW). As temperature rises, the hydrogen bond number for hydrating water decreases below ~373 K because of the SD → SHW transition and increases afterward owning to the ion pairing.